Immobilization of Pt Nanoparticles in Carbon Nanofibers: Bifunctional Catalyst for Hydrogen Evolution and Electrochemical Sensor. (10th June 2015) - Yang, Tingting; Du, Mingliang; Zhu, Han; Zhang, Ming; Zou, Meiling
Highlights: PtNPs/CNFs were synthesized via electrospinning and carbonization process. PtNPs were evenly dispersed in CNFs without aggregation. The PtNPs/CNFs can serve as bifunctional catalyst. The PtNPs/CNFs exhibits promising catalytic activity and excellent stability. Abstract: A facile strategy for the preparation of novel Pt nanoparticles/carbon nanofibers (PtNPs/CNFs) nanostructure by combining the electrospinning and carbonization process is demonstrated. PtNPs were obtained in polyacrylonitrile nanofibers (PANFs) through an in situ reduction as well as electrospinning, and then the PtNPs/PANFs nanostructure was converted to PtNPs/CNFs following a carbonization process. The formation and structure of the synthesized PtNPs/CNFs nanostructure were systematically characterized, suggesting that PtNPs with diameter of ca. 8.8 nm were evenly dispersed in CNFs and nearly no aggregation was observed. The results indicate that the nanostructure possesses high catalytic activity for both hydrogen evolution reaction (HER) and electrochemical sensor, as well as long-term stability for HER, serving as a bifunctional catalyst. The present investigations provide a general route for the fabrication of novel electrocatalyst, which may also be extended to synthesize other metal nanoparticles/CNFs nanostructures.